2017
DOI: 10.1101/170423
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Opposing effects of floral visitors and soil conditions on the determinants of competitive outcomes maintain species diversity in heterogeneous landscapes

Abstract: 13Theory argues that both soil conditions and aboveground trophic interactions are equally important for 14 determining plant species diversity. However, it remains unexplored how they modify the niche di erences 15 that stabilise species coexistence and the average fitness di erences driving competitive dominance. 16We conducted a field study in Mediterranean annual grasslands to parameterise population models 17 of six competing plant species. Spatially explicit floral visitor assemblages and soil salinity v… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 37 publications
(62 citation statements)
references
References 47 publications
3
59
0
Order By: Relevance
“…Importantly, this aligns with recent studies that show plant–pollinator interactions can alter competitive hierarchies among plant species (Pauw , Lanuza et al. ). Extending this concept from our cage experiment to consider a natural system, we suggest that differences in plant species’ competitive abilities to attract pollinators could well contribute to maintaining the skewed species abundance distributions that are common in natural plant communities (McGill et al.…”
Section: Discussionsupporting
confidence: 90%
“…Importantly, this aligns with recent studies that show plant–pollinator interactions can alter competitive hierarchies among plant species (Pauw , Lanuza et al. ). Extending this concept from our cage experiment to consider a natural system, we suggest that differences in plant species’ competitive abilities to attract pollinators could well contribute to maintaining the skewed species abundance distributions that are common in natural plant communities (McGill et al.…”
Section: Discussionsupporting
confidence: 90%
“…Facilitation can only foster coexistence if rare species benefit disproportionately in relation to the abundant species (Soliveres et al ). Thus, plants’ pollination niches may represent an axis stabilising plant interspecific competition (Benadi & Pauw ; Lanuza et al ; Johnson & Bronstein ). Nevertheless, landscape‐level NDD was only marginally significant for pollen tubes.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, accomplishing this type of experiment is a high time‐consuming task but prior work has shown that it is doable (Saavedra et al, ). In case this approach is not feasible for conservation or logistical issues, another possibility is to use information of natural variation in species abundances and their reproductive outputs across landscapes together with the underlying environmental factors accounting for such variation (Bimler, Stouffer, Lai, & Mayfield, ; Lanuza, Bartomeus, & Godoy, ). Finally, a possibility that works either well is to use temporal variation instead of spatial variation.…”
Section: Facing the Main Problem Of The Structural Stability Framewormentioning
confidence: 99%